A Simulation Framework for Sustainability Assessment in Evolving Socio-Technical Infrastructure Systems. (2016) - Batouli, Mostafa; Mostafavi, Ali
Abstract: Sustainability of infrastructure systems involves multiple interrelated objectives which are dependent on the dynamic behaviors of stakeholders, interdependencies between infrastructure assets, and evolving conditions in the social and environmental systems. This research contributes to the body of knowledge by creating a framework that integrates: (1) different dimensions of sustainability in infrastructure networks, and (2) dynamic changes in the behaviors of stakeholders, asset performance conditions, and the social and environmental conditions. The proposed framework includes an agent based simulation model to capture the dynamic behaviors of decision makers and the evolving performance of infrastructure assets under different socio-environmental conditions. The outcomes of the simulation model include the short- and long-term costs and environmental impacts of infrastructure networks under different scenarios related to the changes in the socio-environmental conditions. The application of the framework is shown in a numerical case study of a road network. The results include: (i) identification of infrastructure management strategies (e.g., maintenance planning and funding allocation) that optimize the tradeoff between annual cost and environmental impacts of the network; and (ii) discovering robust management strategies that lead to highly-likely desired sustainability outcomes across different uncertain scenarios related to the future socio-environmental conditions. The results show the capability of the proposed framework for sustainability assessment of infrastructure systems based on integrated analysis of the dynamic behaviors of decision-makers, infrastructure characteristics, and evolving socio-environmental conditions. Hence, it provides a predictive quantitative tool to inform decision-making and policy formulation toward improving the sustainability of infrastructure networks.